1984
DOI: 10.1128/aac.26.5.670
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus saprophyticus beta-lactamase production and disk diffusion susceptibility testing for three beta-lactam antimicrobial agents

Abstract: ,B-Lactamase production and MIC determinations for penicillin, methicillin, and cephalothin were assessed for 67 strains of Staphylococcus saprophyticus and correlated with results of disk diffusion susceptibility testing. Fifty-five (82%) of the 67 strains produced 14-lactamase, and 40 (77%) of these ,B-lactamase-producing strains were susceptible (zone size, >29 mm) by disk diffusion techniques. Although the range of zone sizes for ,-lactamase producers was broad (26 to 36 mm), all 38 strains with a zone siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
(15 reference statements)
1
7
1
Order By: Relevance
“…Determination of/3-Iactamase production from the zone edge appearance resulted in a large number of false positive results, contrary to findings of other investigators (7) (7,13). It is evident that file sharp zone edge can be formed due to/3-1actamase production as well by other, as yet undetermined factors.…”
Section: Discussioncontrasting
confidence: 76%
“…Determination of/3-Iactamase production from the zone edge appearance resulted in a large number of false positive results, contrary to findings of other investigators (7) (7,13). It is evident that file sharp zone edge can be formed due to/3-1actamase production as well by other, as yet undetermined factors.…”
Section: Discussioncontrasting
confidence: 76%
“…saprophyticus have yielded inconsistent and methoddependent results (15,20,27,44), these organisms had a unimodal distribution of penicillin G MICs (5,15,33,39). Based on our studies, we concluded that all strains either were ,-lactamase negative or produced ineffective enzyme and were susceptible to penicillin G; application of S. aureus MIC criteria was not appropriate to S. saprophyticus.…”
Section: Discussionmentioning
confidence: 90%
“…According to Hovelius and Mardh [60], chromogenic cephalosporin (nitrocefin) does not detect β-lactamase production in S. saprophyticus . In contrast, Latham et al [61] identified β-lactamase production by the chromogenic cephalosporin method in 50 (75%) of 67 S. saprophyticus isolates. McDougal and Thornsberry [62] evaluated β-lactamase production in 66 S. aureus strains using the nitrocefin disk test and all strains tested positive.…”
Section: Discussionmentioning
confidence: 99%